Doa-doa pilihan & manzil (My Qalam Technology School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2005)
Al-Quran learning package using pen reader. Its point and read any Ayah/Surah, store extra MP3 audio in pen, extra qari/recitors, quran audio translations, and other features.